2006
DOI: 10.1016/j.amjhyper.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability and Cardiovascular Risk in Treated Hypertensive Patients

Abstract: Increased BP variability is associated with higher incidence of cardiovascular events, but also with other relevant prognostic factors. Indeed, in multivariate analysis the possible adverse prognostic impact of BP variability is no longer evident. Thus, in treated hypertension, BP variability evaluated by noninvasive monitoring is not an independent predictor of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 34 publications
0
33
0
2
Order By: Relevance
“…Possible limitations of previous studies were a lack of statistical power, 2-5 selection of specific groups of patients, [5][6][7] categorization of variability by arbitrary cutoff points, 2,4,[7][8][9] and sole reliance on fatal end points. 10,11 Moreover, various parameters can capture short-term blood pressure variability over 24 hours, but most studies only considered the SD of systolic 4,6,12 or diastolic blood pressure or both.…”
mentioning
confidence: 99%
“…Possible limitations of previous studies were a lack of statistical power, 2-5 selection of specific groups of patients, [5][6][7] categorization of variability by arbitrary cutoff points, 2,4,[7][8][9] and sole reliance on fatal end points. 10,11 Moreover, various parameters can capture short-term blood pressure variability over 24 hours, but most studies only considered the SD of systolic 4,6,12 or diastolic blood pressure or both.…”
mentioning
confidence: 99%
“…Possible limitations of previous studies were lack of statistical power, 38-41 selection of specific groups of patients, [41][42][43] categorization of variability by arbitrary cut-off points, 38,40,[43][44][45] and sole reliance on fatal end points. 46,47 Moreover, various parameters can capture short-term BP variability over 24 h, but most studies only considered the s.d.…”
Section: Short-term Bp Variabilitymentioning
confidence: 99%
“…However, the predictive value of BPV concerning cardiovascular and all-cause mortality has long been a matter of debate. [3][4][5][6][7][8][9] More recently, nighttime BPV was considered to be a more pronounced risk factor than daytime BPV. 10,11 Finally, Rothwell 12 showed that visit-to-visit BPV was an independent and strong predictor of cardiovascular events, such as stroke and coronary heart disease, and calcium channel blockers and nonloop diuretics were the most effective antihypertensive agents in reducing BPV and in preventing stroke.…”
mentioning
confidence: 99%